Om Grundtvigs udviklingslære - og noget om Darwins - Korsgaard, Ove (Grundtvig-studier, 2011)
Om Grundtvigs udviklingslære - og noget om Darwins[About Grundtvig ’s theory of evolution - and something about Darwin ’s]By Ove Korsgaard The idea expressed in the Danish word “udvikling” (meaning both ‘development’ and ‘evolution’) forms a principal category in the works of, respectively, Grundtvig and Darwin. However, while Darwin studied nature, Grundtvig was primarily preoccupied with history. Grundtvig’s two-front war against materialism and idealism is reflected in a great part of his writings. As far as nature is concerned, he was looking for a third position offering a different stance compared to the trends dominating in contemporary theology and natural science. Departing from his essay “ On Man’s Condition in the World” from 1817, Grundtvig started to sketch a theory of evolution based upon a model of nature depicted as a ladder with each step representing a particular quality. Mineral kingdom stands for form, vegetable kingdom additionally for life, animal kingdom supplements with consciousness and, finally, human beings with self-consciousness. According to Grundtvig, it is the interaction between “hand and mouth” - from the grip of the hand to an understanding expressed in language - that is the most important motivating drive in the development of self-consciousness. In an epilogue, the author refers to natural scientist Jesper Hoffmeyer, who questions whether Darwin in his works on evolutionism did offer an exhaustive explanation of evolution. Hoffmeyer himself refuses to choose between believing in a conception of nature in which an intelligent being cannot possibly feel at home and believing that man becomes a living soul by receiving the breath of God.